âHIDDEN OBJECT MEDIAâ FOR TEACHING ENGLISH AT THIRD GRADE ELEMENTARY STUDENTS IN SD LABORATORIUM UNDIKSHA SINGARAJA - Sari, I. A. P. P. G. (International Journal of Language and Literature, 2017)
This research aimed to (1) analyze the use of âHidden Object Mediaâ in teaching English for third-grade elementary students in SD Lab Undiksha Singaraja. The subject of this research was thirty seven of third grade students in SD Lab Undiksha Singaraja at even semester academic year 2016/2017. This research categorized as descriptive qualitative in the form of graphs and percentage. Some instruments were used to conduct this research. There was interview guide, observation sheet and questionnaire. There are four media that was trying out based on topic of animals and body parts. Each media consist of teacherâs guidelines, brief story, hidden object handout, and list of possible post activities. Based on the result of studentsâ interview and teacherâs questionnaire it was found that hidden object media were able to involve students in learning, able to motivate and help students learn new vocabularies. The percentage shows that more than 78% in every session students felt happy, more than 57% in every session students felt helpful and 100% students feel motivated and feel that the media were good for them to be used. Thus, this media was proper to use for teaching English for third grade students.